Screening of chronic radiation proctitis and colorectal cancer using periodic total colonoscopy after external beam radiation therapy for prostate cancer. (23rd April 2021) - Nakamura, Yuki; Soma, Takahiko; Izumi, Keita; Sakai, Yasuyuki; Ushijima, Hiroki; Kudo, Shigehiro; Saito, Yoshihiro; Kageyama, Yukio
Abstract: Objective: To investigate the incidence of colorectal cancer and chronic radiation proctitis after prostate radiotherapy using periodic total colonoscopy screening. Methods: From February 2013 to January 2018, 270 patients who underwent external beam radiation therapy for prostate cancer were advised to receive periodic total colonoscopy screening annually. We evaluated the incidence and characteristics of colorectal cancer and chronic radiation proctitis. Results: First, second, third, fourth and fifth total colonoscopy were performed in 256 (95%), 151 (56%), 60 (22%), 23 (8.5%) and 7 (2.6%) patients at a median of 14, 31, 42, 54 and 72 months after radiotherapy, respectively. The prevalence proportion of colorectal cancer in the first colonoscopy since radiotherapy was 3.9%. Twelve (4.4%) patients were diagnosed with colorectal cancer, including four invasive cancers, during a follow-up period. Eight of these 12 patients had not experienced rectal bleeding. The median time to diagnosis of colorectal cancer was 21 months. Chronic radiation proctitis was observed in 136 (50%) patients, including 67 (25%) patients with symptomatic bleeding. Conclusions: The high detection rate of asymptomatic radiation proctitis suggests the utility of total colonoscopy to screen for early-stage colorectal cancer prior to or following radiotherapy for prostate cancer. Considering the longevity after localized prostate cancer treatment, the awareness of chronic radiation-induced proctitis and the risk of colorectal cancer masked by bleeding is needed in treatment decision -making. Abstract : Periodic total colonoscopy screening after external beam radiation therapy for prostate cancer revealed incidental colorectal cancers and the high incidence of asymptomatic radiation proctitis.